The power of suggestion: Disclosure ideologies and medically assisted death (Medicine Anthropology Theory, 2019)
This article examines an ethical controversy that has received relatively little attention in public debates about the legalization of medical aid-in-dying (AID): should physicians inform patients that they have the option of hastening death? Drawing on ethnographic research about the implementation of AID in Vermont, I argue that how we understand the moral stakes of this debate depends on divergent views regarding language use in social interactions. Some stakeholders in this debate view a physician’s words as powerful enough to damage the patient-physician relationship or to influence a patient to hasten her death, while others believe that merely informing patients about AID cannot move them to act against their own values and preferences. I illustrate how these divergent perspectives are tied to competing language ideologies regarding clinical disclosure, which I call ‘disclosure ideologies’. My analysis of these two disclosure ideologies surrounding AID highlights disclosure practices in medicine as a rich site for medical anthropological theorizing on linguistic performativity and the social power of clinical language.